A Concise History of the Arabs - McHugo, John (London Saqi, 2013)
John McHugo takes the reader on a journey through the political, social and intellectual history of the Arabs from the Roman Empire right up to the present day
Include Bibliography and Index
Keywords: Arab countries -- History -- Arabs -- History